A Study of Proteolytic and Fibrinolytic Factors in the Human Prostate - Nijs, Michelle; Brassinne, Christiane; Coune, A; Tagnon, H. J (Thrombosis and Haemostasis, 1971)
An analysis of the proteolytic factors contained in human prostatic tissue was performed in vitro. Casein, fibrinogen and fibrin, non-radioactive and radioiodinated were used as substrates.A first factor, called direct proteolytic activity, capable of proteolyzing casein without prior activation, is described. It had no effect on fibrinogen or fibrin, was inhibited by epsilon aminocaproic acid, but not by the soybean trypsin inhibitor. This shows that this proteolytic activity was quite different from plasmin.A second factor, called plasminogen proactivator, was demonstrated on bovine plasminogen in the presence of streptokinase, the latter being unable to produce direct activation of bovine plasminogen. Activation of this system resulted in the transformation of plasminogen into plasmin, capable of digesting casein as well as fibrinogen and fibrin. Epsilon aminocaproic acid and the soybean trypsin inhibitor inhibited this system. The properties of this proactivator show that it probably does not result from the presence of small amounts of plasminogen in the prostate. Urokinase, a factor present in human urine, is able to activate this proactivator under certain conditions.The third factor, called plasminogen activator, was capable of activating directly human plasminogen into plasmin. It was not active on bovine plasminogen. Epsilon aminocaproic acid and the soybean trypsin inhibitor were effective inhibitors. Addition of large volumes of human prostatic extract to human plasminogen resulted in a paradoxical decrease of the proteolytic activity suggesting the possible existence in the prostate of an inhibitor of this third factor.Possible relationships between these factors and the clinical state of fibrinolysis observed in some cases of disseminated prostatic cancer are discussed.